Transformations of the Struggle for Social and Political Rights: Democratic Politics of Contestation in a Post-Republican Era - Oliver Flügel-Martinsen (Social Work and Society)
From the 1970s to today we have witnessed a far-reaching transformation of emancipatory politics, especially in light of the radical pluralization of social and political movements denouncing universalism as oppressive. In this article, I ask how political theory must be reworked in order to provide a critical account of a democratic politics of contestation that is able to deal with these challenges. First, I sketch out why we are moving towards a democratic society of singularities and what that means for a critical understanding of political theory. Second, I offer a brief discussion on some important considerations on the theory of justice implied by these changes. The article then closes with some thoughts on how to move from a republican democratic ideal to a radical democratic practice of critique.